REMOVAL OF HIGH CONCENTRATION HEAVY METALS IN AQUEOUS SOLUTION BY ADSORPTION COLUMN CONTAINING MODIFIED SILICA ADSORBENT FROM RICE HUSK ASH - Thaikam, Nilawan; Tungkananuruk, Kanita; Semvimol, Noppawan (Srinakharinwirot University Journal of Sciences and Technology, 2021)
Rice husk ash is an agricultural waste which has properties as adsorbent material. This research aims to improve heavy metals removal efficiency of silica from rice husk by coating with manganese (IV) oxide. Micro-silica was prepared from rice husk by sol-gel method and coated with KMnO4 at ratio of 1 g KMnO4 to 20 g silica. The removal efficiency of lead (Pb), nickel (Ni), cadmium (Cd) and zinc (Zn) ions in wastewater from electroplating industrial wastewater. From batch experiments, at pH 4 to pH 7 of the 40 mg/L of each metal ion solution and agitation time 60 mins, the adsorption percentages of 4 heavy metal ions were over 94%. The adsorption capacities were 4.01, 3.95, 3.86 and 3.92 mg/g respectively. The adsorption mechanisms were according to both of Langmuir and Freundlich isotherm. In addition, the column model was brought to apply for real work. The 8 g of silica which coated with manganese (IV) oxide was packed into syringe and passed the mixed 4 heavy ions solution through the packing and collected the effluent in every 200 mL. The results revealed that the concentration of lead, nickel, cadmium and zinc were not over the agreement of the effluent standard of industrial estate until the solution was treated at 800, 600, 600 and more than 4,000 mL respectively. Moreover, at the same amount of silica which coated with manganese (IV) oxide, this method gave a good efficiency better than the batch method.